Hubungan Perilaku Personal Hygiene Saat Menstruasi dengan kejadian pruritus vulvae pada remaja di MTS Negeri 1 Manado - Winta Soamole; Nelawati Radjamuda; Suwandi I Luneto3 (Jurnal Ners, 2025)
Pruritus vulvae is a disorder characterized by a sensation of severe itching from the female external genital organs. The highest incidence of pruritus vulvae in the world occurs in adolescents due to poor personal hygiene behavior during menstruation. The aim of this study was to determine the relationship between personal hygiene behavior during menstruation and the incidence of pruritus vulvae in adolescents at MTS Negeri 1 Manado. The research method uses quantitative correlational with a cross sectional approach, the population is 140 consisting of 9 classes with 59 students as respondents, and the sample collection method is purposive sampling carried out on November 21 2024. The research instrument uses a questionnaire sheet and consisting of 26 with univariate statement then the data analyses using frequency distribution and bivariate data analysis using Spearman correlation.The research found the most respondents on age categorize were 12 years old (78%), most respondents had poor personal hygiene behavior (86.4%) and most respondents experienced pruritus vulvae (71.2%). The conclusion of this research p = 0.000, where α <0.05, which means that Ha is accepted and H0 is rejected, meaning that there is a relationship between personal hygiene behavior during menstruation and the incidence of pruritus vulvae in teenagers at MTS Negeri 1 Manado.